2017
DOI: 10.18632/oncotarget.17484
|View full text |Cite
|
Sign up to set email alerts
|

Charge reversible calcium phosphate lipid hybrid nanoparticle for siRNA delivery

Abstract: Bcl-2 gene is an important target to treat lung cancer. The small interference RNA (siRNA) of Bcl-2 gene (siBcl-2) can specifically silence Bcl-2 gene. However, naked siBcl-2 is difficult to accumulate in the tumor tissue to exert its activity. In this paper, a calcium phosphate lipid hybrid nanoparticle that possessed charge reversible property was prepared to enhance the activity of siBcl-2 in vivo. The average diameter and zeta potential of siBcl-2 loaded calcium phosphate lipid hybrid nanoparticles (LNPS@s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…To make the system pH-triggered charge-reversible, citraconic as a derivative of a maleic amide has been conjugated with cholesterol-aminocaproic acid to coat calcium phosphate particles and the further surface has been tuned by depositing the siRNA. In the last, the positively charged lipid 1,2-dioleoyl-3-trimethylammonium-propanechloridesalt (DOTAP) and negatively charged lipid dioleoylphosphatydicacid (DOPA) has been added and the charge reversal was investigated with the reversal of zeta potential results, which successfully suppress the Bcl-2 without inducing any toxicity in lung cancer A549 cells [ 50 ]. In some cases, the carrier should be negatively charged to achieve efficient transfection whilst positively charged in an acidic endolysosome environment to inhibit its uptake by disrupting the endolysosomal membrane.…”
Section: Strategies In Bone Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…To make the system pH-triggered charge-reversible, citraconic as a derivative of a maleic amide has been conjugated with cholesterol-aminocaproic acid to coat calcium phosphate particles and the further surface has been tuned by depositing the siRNA. In the last, the positively charged lipid 1,2-dioleoyl-3-trimethylammonium-propanechloridesalt (DOTAP) and negatively charged lipid dioleoylphosphatydicacid (DOPA) has been added and the charge reversal was investigated with the reversal of zeta potential results, which successfully suppress the Bcl-2 without inducing any toxicity in lung cancer A549 cells [ 50 ]. In some cases, the carrier should be negatively charged to achieve efficient transfection whilst positively charged in an acidic endolysosome environment to inhibit its uptake by disrupting the endolysosomal membrane.…”
Section: Strategies In Bone Targetingmentioning
confidence: 99%
“…Moving ahead, the research has been proposed by Cai et al [ 50 ], wherein calcium phosphate–lipid hybrid nanoparticles are associated with the charge reversal property were synthesized for gene silencing purposes in lung cancer. SiRNA Bcl-2 gene via phosphate–lipid hybrid nanoparticles successfully reached the cytoplasm and expression of Bcl-2 in A549 cells.…”
Section: Strategies In Bone Targetingmentioning
confidence: 99%
“…The impact of the nanomaterials' surface charge on their ability to penetrate spheroids has also been a studied subject [43,[76][77][78][79][80][81]. In this regard, Jiang group demonstrated that negatively charged polystyrene-based nanoparticles (ζ potential of -34.9 mV) have a better ability to penetrate HepG2 spheroids when compared with their positively charged equivalents (+9.2 mV) [43].…”
Section: Nanomedicines' Chargementioning
confidence: 99%
“…The haemolysis effect of DSPE-DEX and DSPE-DEX-ALN was evaluated by using UV-Vis spectrophotometer [21].…”
Section: Cytotoxicity Of Dox@dbms-alnmentioning
confidence: 99%